Networks of Passing: Experiences of Undocumented Latin American Immigrants' Identity Negotiation. Issue 6 (1st November 2016) - Scranton, Audrey; Afifi, Tamara; Afifi, Walid; Gangi, Katlyn
Abstract: Undocumented Latin American immigrants are one of the fastest-growing populations in the United States, and they are one of the most vulnerable. Due to constant fear of deportation, these immigrants have to communicatively "pass" for documented in a variety of situations, and they might be likely to use informal network ties (social capital) to do so. Through eight diverse focus group interviews of undocumented immigrants, this study explores how this population passes. Undocumented immigrants used talk, the body, or documents to pass either individually or through network members. Implications for both theory and practice are discussed.